107k views
1 vote
Helppppppppppppppppppppppp

Helppppppppppppppppppppppp-example-1

2 Answers

5 votes
(2x + 3) ^ 2 + 8 (2x + 3) + 11 = 0
Using substitution we have:
u = 2x + 3
We rewrite:
(u) ^ 2 + 8 (u) + 11 = 0
We use resolvent:
u = (- b +/- root (b ^ 2 - 4ac)) / (2a)
We replace:
u = (- (8) +/- root ((8) ^ 2 - 4 (1) (11))) / (2 (1))
u = (- (8) +/- root (64 - 44)) / (2)
u = (- (8) +/- root (20)) / (2)
u = (- (4) +/- root (5))
We return the change:
u = (- (4) +/- root (5)) = 2x + 3
We clear x:
x = (- (7) +/- root (5)) / 2
Answer:
x = (- (7) +/- root (5)) / 2
(option2)
User Evan L
by
5.4k points
7 votes
Answer:
The second choice is the correct one

Step-by-step explanation:
(2x+3)^2 + 8(2x+3) + 11 = 0
To use the u substitution, we will assume that:
2x + 3 = u

Substitute with this in the given expression, we will get:
u^2 + 8u + 11 = 0

The general form of the second degree equation is:
ax^2 + bx + c = 0

Comparing the expression we reached with the general one, we will find that:
a = 1
b = 8
c = 11

The roots can be found using the rule found in the attached picture.
This means that, for the given expression:
u = -4 ± √5

Now, we have:
u = 2x+3
This means that:
at u = -4 + √5
2x + 3 = -4 + √5
2x = -7 + √5
x = (-7 + √5) / 2

at u = -4 - √5
2x + 3 = -4 - √5
2x = -7 - √5
x = (-7 - √5) / 2

This means that, for the given expression:
x = (-7 ± √5 ) / 2

Hope this helps :)
Helppppppppppppppppppppppp-example-1
User Avgvstvs
by
6.0k points